Implantation of mitral, aortic, and tricuspid bioprostheses due to infective endocarditis with necessary reimplantation of the bioprosthetic aortic valve - Danielecki, Cezary; Bugajski, Paweł; Olszewski, Roman; Greberski, Krzysztof; Kalawski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The patient was admitted to the Department of Cardiac Surgery of the J. Struś City Hospital in Poznan due to infective endocarditis involving the aortic, mitral, and tricuspid valves. Implantation of three biological valve prostheses proceeded without complications. Starting on day 23, the patient’s general condition deteriorated, with high fever. Despite postoperative antibiotic therapy, transesophageal echocardiography revealed the presence of vegetation on the bioprosthetic aortic valve. On the 46th day after the initial surgery, the patient required replacement of the aortic bioprosthesis, which exhibited the presence of numerous vegetations. The bioprosthetic mitral and tricuspid valves were not affected by the degenerative process. On the 12th day after the reimplantation of the bioprosthetic aortic valve, the patient was discharged from the hospital in good general condition.